Adoption of Digital-Based Management Information Systems and Its Impact on MSME Performance in Indonesia - Edi Nurachmad; Mumuh Mulyana; Anton Sukamto; Isnan Mulia (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The rapid advancement of digital technology has compelled Micro, Small, and Medium Enterprises (MSMEs) to adopt digital solutions in order to enhance competitiveness and ensure business sustainability. One of the most critical digital infrastructures supporting managerial effectiveness is the adoption of digital-based Management Information Systems (MIS), which enable integrated data processing and data-driven decision-making. This study aims to empirically examine the impact of digital-based MIS adoption on MSME performance in Indonesia. Using a quantitative explanatory approach, primary data were collected from MSME owners and managers operating across various business sectors. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess both the measurement and structural models. The results indicate that digital-based MIS adoption has a positive and statistically significant effect on all dimensions of MSME performance, including financial, operational, market, and innovation performance. Among these dimensions, operational performance exhibits the strongest relationship, highlighting the role of digital MIS in improving process efficiency and operational control. The findings confirm that digital-based MIS functions as a strategic organizational resource that enhances MSME competitiveness in the digital economy. This study contributes to the literature on digital transformation and MSME performance by providing empirical evidence from an emerging economy context and offers practical implications for MSME owners and policymakers in accelerating digital adoption. Keywords: digital-based MIS, MSME performance, digital transformation, PLS-SEM, Indonesia